Syntactic descriptions of bilingual patterns - Ganeshsundaram PC; Maya Devi (Journal of All India Institute of Speech and Hearing, 1970)
Language contact is a Universal phenomenon, having a tendency towards cultural harmony as one of its manifestations. This brings into effect the operation of phenomenon which is of Sociolinguistic importance. One of the resultants of this phenomenon which is of significance to psycholinguistics is 'Interlinguistic Interference'.